EVALUATION OF THE GENOTOXIC EFFECTS OF MITOMYCIN C ON THE EXAMPLE OF APOE KNOCKOUT MICE - M. A. Asanov; M. YU. Sinitsky (Байкальский медицинский журнал)
BACKGROUNDMitomycin C (MMC) has a wide spectrum of genotoxicity, including inhibition of DNA synthesis, clastogenesis and mutagenesis. As an immediate-action clastogen requiring exclusively intracellular reductive activation, MMC initiates efficient DNA cross-linking. Most studies are aimed at studying single-stage acute effects, which are caused by high doses of mutagen. In turn, there are no or very few studies aimed at studying the chronic effects of MMC. Polychrome red blood cells have been accepted as a suitable target for the evaluation of micronuclei in both acute and cumulative injury. The in vivo micronucleus test is well established as a standard assay for assessing genotoxicity at the chromosomal level of mouse erythrocytes.THE AIM OF THE STUDYTo create a chronic genotoxic effect of mitomycin C without lethal outcome in ApoE knockout mice while selecting the optimal dose of MMC.MATERIALS AND METHODSThe study design included 6 groups of ApoE-/- mice, two doses of MMC with a concentration of 0.1 and 0.5 mg/kg, one-time and three-time administration. To assess genotoxicity, 1000 polychrome erythrocytes (PCEs) extracted from the bone marrow of a mousefemur were counted on each sample, and PCEswith micronuclei were identified.RESULTSThis study aimed to find the optimal dose of MMC that has a clear genotoxic effect and does not lead to death in an ApoE knockout mouse model. With a single injection, PCEs with chromosomal damage were more common (more than 2 times; p < 0.05) in groups of mice with MMC administration (0.1 and 0.5 mg/kg; 0.39 % and 0.26 %, respectively) compared to the control group (0.15 %). We also found that the frequency of occurrence of PCEs with micronuclei in groups of mice with MMC dose of 0.1 and 0.5 mg/kg (0.36 % and 0.47 %, respectively) and three-time administration exceeded this indicator in mice from the control group (0.2 %).CONCLUSIONThe present study on the determination of the optimal dose of mitomycin C provides further evidence that 0.1 mg/kg is the threshold value for genotoxic effects caused by MMC. An increase in the frequency of micronucleated immature red blood cells in animals exposed to a mutagen is an indicator of induced structural or numerical chromosomal aberrations. Our results further suggest that careful selection of MMC dose is critical. Dose-response studies in rodents can provide useful information on mechanisms and dose selection for long-term toxicity studies.